Abuse or Slavery? A Look at Practices of Debt Peonage from the 19th-Century Philippines - Carolina Hiribarren Cardoen (Rechtsgeschichte - Legal History)
This article problematizes the work system known as debt peonage that developed throughout the Spanish-controlled territories of the Philippine islands, examining memorias and colonial sources to analyze practices of abuse that this system sustained during the 19th century. It illustrates the diversity of work experiences imposed on Indigenous peoples. Debt peonage involved a large part of colonial society and could result in a variety of situations, ranging from the imposition of excessive interest rates to what some scholars have considered slavery-like conditions.